Penguatan Gender Dalam Pendidikan Islam - Asmuni Asmuni; Darwin Eka Saputra; Robiyanto Robiyanto; Bastomi Bastomi; Kasinyo Harto; Tutut Handayani (Departement of Mathematics Education, 2024)
Issues related to gender issues have been discussed since humans existed in this world. Discriminatory acts against women occur because the patriarchal culture that has existed for thousands of years has become the doctrine that women are considered as people who do not need to be involved in economic, political, religious, and even educational matters. Social inequality which considers that women do not need to have a high formal education causes a lot of crime and violence against women. Even in the Islamic religion itself, women are greatly elevated in rank even though in some aspects there are boundaries that have been determined by religion. This paper uses the method research library by collecting various literature related to the discussion of gender strengthening in Islamic education.